Neural Correlates of Resilience in Pediatric Concussion and the Influence of a Mindfulness-Based Intervention - Brown, Olivier (Université d'Ottawa | University of Ottawa, 2025)
Concussion is the most common form of brain injury. It disproportionately affects children and adolescents, as they face heightened risk of head injury. Emerging evidence suggests psychological resilience mitigates clinical symptom burden from pediatric concussion. Mindfulness-based interventions (MBIs) may enhance resilience, thereby affecting recovery trajectories. More advanced imaging research of pediatric concussion is required to better understand the neural correlates of resilience in this context as well as whether MBIs moderate associations between resilience and neural outcomes. This dissertation presents an evidence-based framework depicting mechanisms by which resilience may affect neural outcomes following concussion, as well as ways that MBI may influence resilience and moderate neurofunctional correlates of resilience. This work includes three studies from multi-site pediatric concussion trials. Studies 1 and 2 were based on data from the Pediatric Concussion Assessment of Rest and Exertion trial (Clinicaltrials.gov identifier: NCT02893969). Study 1, a case-control study, examined associations between resilience and white matter microstructure in adolescents with acute concussion (n=66) and orthopedic injury (n=29). Resilience was measured by the Connor-Davidson Resilience Scale 10 at baseline, reflecting experiences over the preceding 30 days, and white matter microstructure (fractional anisotropy, mean, axial, and radial diffusivity) was assessed via diffusion tensor imaging at baseline and follow-up. Results revealed negative correlations between baseline resilience and fractional anisotropy, and positive correlations between baseline resilience and both mean and radial diffusivity in the concussion group. Study 2, also a case-control study (concussion n=67, orthopedic injury n=30), examined associations between resilience and resting-state functional connectivity of the default mode network (DMN), salience network (SN), and central executive network (CEN) at baseline and follow-up. Seed-to-voxel analyses showed a positive correlation between resilience and CEN connectivity in the concussion group, with group moderating associations involving SN and DMN connectivity. Study 3, a study from the Mindfulness-Based Intervention for Mild Traumatic Brain Injury trial (ClinicalTrials.gov identifier: NCT05105802), explored whether an MBI influenced resilience trajectories and moderated the association between baseline resilience and functional connectivity at 4 weeks post-injury (MBI n=16, cognitive sham control n=20). While MBI did not significantly impact resilience trajectories, significant group-by-resilience interactions were observed in relation to connectivity of the DMN (intention-to-treat and per-protocol), SN (per-protocol), and CEN (per-protocol). Together, these studies provide a foundation for understanding the neural underpinnings of resilience following pediatric concussion, providing evidence of significant associations of resilience with white matter microstructure and functional connectivity, as well as the moderating role of MBI. The findings explored in this dissertation support an empirical evidence-based framework of resilience and MBI in pediatric concussion outcomes, warranting future initiatives to improve our understanding of the potentially beneficial effects that resilience may have on brain health of children and adolescents with concussion.
Keywords: resilience; concussion; pediatric; mindfulness; MRI